Acupuncture for the Treatment of Tension-Type Headache: An Overview of Systematic Reviews. (19th March 2020) - Huang, Jinke; Shen, Min; Qin, Xiaohui; Guo, Weichi; Li, Hui
Abstract : Objectives . Because current evidence regarding the effectiveness of acupuncture for a tension-type headache (TTH) is controversial, we evaluated the reliability of the methodological quality and outcome measures of systematic reviews/meta-analyses (SRs/MAs) on acupuncture for TTH. Methods . We conducted a comprehensive literature search for SRs/MAs in major databases from the database's inception to September 2019. The Methodological Quality of Systematic Reviews 2 (AMSTAR-2) and the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) assessments were used to assess the methodological quality of the included reviews and the quality of evidence, respectively. Results . Eight reviews were included in the analysis. The AMSTAR-2 assessment results showed that the methodological quality of all included reviews was critically low. Thirty-six outcome measures were included in these reviews. The GRADE results showed that 25 (25/36, 69.4%) outcomes provided low- or very low-quality evidence, four (4/36, 11.1%) provided moderate-quality evidence, and seven (7/36, 19.4%) provided high-quality evidence. Descriptive analysis results showed that acupuncture treatment for TTH reduced headache frequency and severity. Conclusions . Acupuncture appears to be an effective treatment modality for TTH, but the credibility of the results is limited owing to the generally low methodological quality and evidence quality in the included SRs/MAs.